Pelatihan Digital Marketing Dalam Memasarkan Produk Badan Usaha Milik Desa - Nani, Paskalis A.; Lopes Amaral, Maria Augustin; Boelan, Erly G.; Baunsele, Anselmus; Sinlae, Alfry Aristo Jansen; Ketmoen, Adrianus (Bakti Cendana, 2023)
This non-profit activity was carried out by the teaching team of Widia Mandira Catholic University as part of BUMDes digital marketing training in Parity and Oeteta villages. This training aims to provide digital marketing knowledge to the managers of Gempar BUMDes in Pariti Village and Lentera Kasih BUMDes in Oeteta Village, which will be implemented from August 3, 2022. The method used is a modern approach with a participatory rural approach in the form of training and mentoring, usually in three stages. Preparation, training and evaluation to better understand the business in her two villages, Parity Village and Oeteta Village. A total of 30 participants, including BUMDes administrators, village governments, community leaders, MSMEs and youth groups from two villages, participated in this training, and the average age was relatively young, including beginners. The results achieved have increased the village`s business knowledge of the importance of digital marketing (DM) to increase the company's sales and sustainability. This activity aims to help stakeholders increase their income in the digital age, increase their knowledge and avoid being eroded by the changing times.